Drug Resistant Tuberculosis in the Northern Region of Zambia: A Retrospective Study - Monde, Ngula; Zulu, Mildred; Tembo, Mathias; Handema, Ray; Munyeme, Musso; Malama, Sydney (Frontiers in Tropical Diseases, 2021)
Abstract Background: Zambia is one of the countries in sub-Saharan Africa affected with multi drug/Rifampicin resistant tuberculosis. However, the drug resistant tuberculosis situation over the years has not been described in various regions of the country. Consequently, this review aims to describe the drug resistant tuberculosis situation in northern regions of Zambia over a four-year period to give an insight on the burden of tuberculosis in this region. This is based on data generated from a Regional Tuberculosis Reference Laboratory. Method: Data was retrospectively reviewed on 232 with available Drug susceptibility testing results over a four-year period (2016-2019). Data was collected from tuberculosis registers and patient request forms and entered into a pre-tested standardized checklist and later entered in Excel Computer software. Double blinded checking was done by two independent data clerks to minimize duplication of cases. Cleaned data was then exported to jamovi software (jamovi version 1.8.1, Sydney, Australia) for analysis. Descriptive statistics were performed and reported as frequencies and graphs. Results: Out of 232 DSTs samples with available DST results, 211 (90.9%) were drug resistant TB while 21 (9%) were drug susceptible. Fifty three percent (124/232) of these were multi-drug resistant Tuberculosis and 32.3% (75/232) were confirmed as Rifampicin Mono-resistance. Only 1.7% (4/232) of the Multi-drug resistant Tuberculosis patients were Pre-extensively drug-resistant Tuberculosis. Copperbelt province had the largest proportion (56%) of multi-drug resistant tuberculosis patients followed by Luapula (48%) and North-Western (30%) provinces. The proportion of MDR-TB in previously treated patients was 88 (41.7%) and 27(12.7%) in new patients. Conclusion and recommendation: There has been a slight increase in the cases of Multi-drug resistant tuberculosis over the four years under review with high rates being recorded on the Copperbelt Province. We therefore recommend strengthened routine laboratory surveillance and improved case management of multi-drug resistant tuberculosis patients in the region.